Inovasi Produk Anyaman Pandan dengan Menerapkan Strategi Desain dalam Produk Modern - Kendall Malik; Ferry Fernando; Yandri; Saftrian Mukhlizul Fuad; Nofrial; Ramadhani Kurniawan; Hanafi Malik (Besaung : Jurnal Seni Desain dan Budaya, 2025)
This study aims to analyze local pandan woven products in West Sumatra, especially Sijunjung Regency, into a more modern product innovation form through strategic design. Pandanus weaving has a long history and strong cultural value but faces challenges such as declining demand due to shifting market preferences and competition from manufactured goods. Using a qualitative and explorative approach through the "Design Strategy" method, this research focuses on integrating natural and synthetic materials by combining pandanus weaving with synthetic leather to create functional, aesthetic, and commercial products. The study explores weaving techniques fused with synthetic materials, resulting in unique colors and characteristics from both the pandanus weave and the synthetic leather. This reveals the potential of pandanus weaving to be applied in product prototypes that cater to market preferences while preserving regional cultural identity. The innovation is expected to not only enhance the competitiveness of pandanus weaving products in the modern market but also introduce design novelty in functional products through material integration. Moreover, it supports the sustainability of the local creative economy and reintroduces the uniqueness of this cultural heritage to a wider audience. The research method involves observation, surveys, and studies of pandanus weaving artisans’ practices, followed by exploration of weaving pattern integration as the main material. The application and assembly technique of synthetic leather to the pandanus weave patterns in various functional product types lead to product innovation.